EFEKTIVITAS SOSIAL MEDIA DAN PEMASARAN INTERAKTIF TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK LOKAL - Nisrina Syawaliyah; Asep Muhamad Ramdan; Dicky Jhoansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
This research was conducted to measure how much influence the effectiveness of social media and interactive marketing influences consumer purchasing decisions. The method used in this research is descriptive and associative with a quantitative approach. The population in this study is made up of users of TikTok Luxcrime's followers in Sukabumi city, using the probability sample method. When conducting this study, 400 respondents were given online questionnaires. The analysis technique employs multiple linear regression with simultaneous and partial influence methods. The findings of this study indicate that the effectiveness of social media on purchasing decisions has a positive and significant impact. Furthermore, interactive marketing positively and significantly impacts purchasing decisions.